The Involvement and Therapy Target of Immune Cells After Ischemic Stroke - Jian, Zhihong; Liu, Rui; Zhu, Xiqun; Smerin, Daniel; Zhong, Yi; Gu, Lijuan; Fang, Weirong; Xiong, Xiaoxing (Frontiers in Immunology, 2019)
After ischemic stroke, the integrity of the blood-brain barrier is compromised. Peripheral immune cells, including neutrophil, T cell, B cell, and macrophage, infiltrate into the ischemic brain tissue and play an important role in regulating the progression of ischemic brain injury. In this review, we will discuss the role of different immune cells after stroke in the secondary inflammatory reaction and focus on the phenotypes and functions of macrophages in ischemic stroke, as well as briefly introduce the anti-cerebral ischemia therapy targeting macrophages.